Detection of reactive oxygen metabolites in malignant and adjacent normal tissues of patients with lung cancer - YÜKSEL, MERAL (BMC, 2013)
Background: Different types of reactive oxygen metabolites (ROMs) are known to be involved in carcinogenesis. Several studies have emphasized the formation of ROMs in ischemic tissues and in cases of inflammation. The increased amounts of ROMs in tumor tissues can either be because of their causative effects or because they are produced by the tumor itself. Our study aimed to investigate and compare the levels of ROMs in tumor tissue and adjacent lung parenchyma obtained from patients with lung cancer. Methods: Fifteen patients (all male, mean age 63.6 +/- 9 years) with non-small cell lung cancer were enrolled in the study. All patients were smokers. Of the patients with lung cancer, twelve had epidermoid carcinoma and three had adenocarcinoma. During anatomical resection of the lung, tumor tissue and macroscopically adjacent healthy lung parenchyma (control) that was 5 cm away from the tumor were obtained. The tissues were freshly frozen and stored at -20 degrees C. The generation of ROMs was monitored using luminol- and lucigenin-enhanced chemiluminescence (CL) techniques. Results: Both luminol (specific for. OH, H2O2, and HOCl-) and lucigenin (selective for O-2(center dot)) CL measurements were significantly higher in tumor tissues than in control tissues (P < 0.001). Luminol and lucigenin CL measurements were 1.93 +/- 0.71 and 2.5 +/- 0.84 times brighter, respectively, in tumor tissues than in the adjacent parenchyma (P = 0.07). Conclusion: In patients with lung cancer, all ROM levels were increased in tumor tissues when compared with the adjacent lung tissue. Because the increase in lucigenin concentration, which is due to tissue ischemia, is higher than the increase in luminol, which is directly related to the presence and severity of inflammation, ischemia may be more important than inflammation for tumor development in patients with lung cancer.
Keywords: Reactive oxygen metabolites; Lung cancer; Oxidative stress; INDUCED OXIDATIVE DAMAGE; SUPEROXIDE-DISMUTASE; RADICAL GENERATION; CHEMILUMINESCENCE; STRESS; EXPRESSION; LARYNX; DNA